The Functional Trajectory in Frail Compared With Non-frail Critically Ill Patients During the Hospital Stay - Fuest, K. E.; Lorenz, Marco; Grunow, Julius J.; Weiss, Björn; Mörgeli, Rudolf; Finkenzeller, Sebastian; Bogdanski, Ralph; Heim, Markus; Kapfer, Barbara; Kriescher, Silja; Lingg, Charlotte; Martin, Jan; et al. (Frontiers in Medicine, 2021)
Background: Long-term outcome is impacted not only by the acute critical illness but also by the functional reserve status at onset, which is reduced by pre-existing frailty. Patients with frailty currently account for up to one third of the critically ill, and they display higher mortality rates. Data on the intrahospital functional trajectory of critically ill patients in relation to frailty is scarce, as prehospital frailty status is often unaccounted. Methods: In this prospective single center cohort study at two interdisciplinary ICUs of a German university hospital, frailty was assessed using the Clinical Frailty Scale (CFS) in adult critically ill patients with an ICU stay >24h. Functional status was assessed using the sum of the subdomains “Mobility” and “Transfer” of the Barthel Index (MTB) at three time points (pre-hospital, ICU discharge, hospital discharge). Results: We included 1172 patients with a median age of 75, and 290 patients (25%) were frail. In a propensity score matched cohort, the probability of MTB deterioration by hospital discharge did not differ in patients with frailty (OR 1.3 [95% CI 0.8-1.9], p =0.301), confirmed in several sensitivity analyses in all patients and survivors only. Conclusion: Despite a reduced functional status, the intrahospital functional trajectory of frail patients was no worse than those of non-frail patients, suggesting a functional rehabilitation potential in critically ill patients with frailty.